Brain susceptibility imaging provides valuable in vivo insights into cerebellar diseases, but biological interpretations remain elusive. Issue 1 (7th February 2022) - Harding, Ian H.; Ward, Phillip G. D.
Abstract : This scientific commentary relates to: 'Quantitative susceptibility mapping reveals alterations of dentate nuclei in common types of degenerative cerebellar ataxias' by Deistung et al . (https://doi.org/10.1093/braincomms/fcab306 ).